(3eLehY aj GdcjejGAs - (3SHGM Hf MfGs
(3ChdgG (B:s
(3bGd GdTjN GdEeGe LGHQ Hf MjGf hbaJ Ydi QSGdI SHGM Hf MfG aEPG gi QSGdI LdjdI eWdYgG CeG HYO aEfi bO LeYJ ddSGOI GdYdeGA hGdMceGA hCXgQJ ef GdYde eG de jLO ai cJGH ZjQ gPG s
(3BNQgG (B:s
(3hjSJMbGf Ydi GdfGQ aEPG EeJRLG HGdSMb Thi Hjf bO Mjf HYO eG jLa ai OhGjI RLGL hJZWjg Edi Cf jYQb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs